A comparative study of low-dose intrathecal bupivacaine 0.5% (heavy), levobupivacaine 0.5% (plain), and levobupivacaine 0.5% (heavy) with fentanyl as an adjuvant in transurethral resection of prostate surgery: A prospective randomized study - Sanyukta Paul; Seema Shende; Neelima Tandon; Deepak R (Asian Journal of Medical Sciences, 2024)
Background: Spinal anesthesia is the technique of choice for transurethral resection of the prostate (TURP) surgeries. Levobupivacaine, an S-enantiomer of bupivacaine, is less cardiotoxic than bupivacaine; therefore, a low dose of local anesthetic with fentanyl as an adjuvant has been used to decrease toxicity and increase efficacy. Aims and Objectives: The aim of this study was to compare and evaluate the efficacy of hyperbaric bupivacaine 0.5%, isobaric levobupivacaine 0.5%, and hyperbaric levobupivacaine 0.5% with fentanyl as an adjuvant. Materials and Methods: One hundred and five patients scheduled for elective TURP surgeries were randomly divided into three groups. Group BH (n=35) received 1.5 mL of 0.5% hyperbaric bupivacaine with 25 μg of fentanyl, Group LH (n=35) received 1.5 mL of 0.5% hyperbaric levobupivacaine with 25 μg of fentanyl, and Group LP (n=35) received 1.5 mL of 0.5% isobaric levobupivacaine with 25 μg of fentanyl intrathecally. Results: The onset of sensory and motor block was earlier and the duration of analgesia and motor block were longer in the BH group (P<0.001) as compared to LH and LP groups. The demographic data, duration of surgery, heart rate, SpO2, pruritus, and shivering were comparable between the groups (P>0.05). The visual analog scale score was higher in the LP group. Hypotension, nausea, and vomiting were seen in the BH group. Conclusion: Hyperbaric is better than isobaric group due to quicker onset and longer duration. Levobupivacaine is better than bupivacaine in terms of the early mobilization and a lesser incidence of side effects, making hyperbaric levobupivacaine a better alternative to isobaric levobupivacaine and hyperbaric bupivacaine.